Exacerbation Of Mycoplasma Gallisepticum By Administration Of Live Infectious Bronchitis Vaccine In Commercial Layer Chickens - Balasubramaniam, A.; Suresh, P.; Eswaran, M. Arthanari; Sukumar , K.; Rajeswar , J. Johnson (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Mycoplasma gallisepticum (MG) infections are commonly known as chronic respiratory disease (CRD) of chickens. The infection with this bacterium is characterized by respiratory rales, coughing, nasal discharge and conjunctivitis (Ley, 2003). Economic losses from condemnation, reduced egg production and increased medication costs make CRD one of the costliest disease problems confronting poultry production. Complicating infections like colibacillosis and some live vaccines are known to result in more sever MG diseases (Mohammad et al., 1987 and Gross, 1990). A case of misdiagnosis leading to use of live infectious bronchitis virus (IBV) vaccine which exaggerated CRD in layer chickens is reported.